The Matter of Formation of Human Being Described By the Holy Quran In Comparison With the History of Embryology - Bashir, Imtiaz; Ikhlaq, Azal; Riaz, Huniya Binte; Ijaz, Farhat; Aftab, Khurram (Universitas Islam Negeri Alauddin Makassar, 2020)
What is the matter of creation of human? This question has been addressed since long back in the history from ancient Indian and Egyptian civilizations to the Greeks and until the advent of modern sciences. The answers to this question were varying and led to various ideologies about the paternity of the newborn and the role and importance of women in society. More or less the concept was that the human is formed from the male semen and female menstrual blood where semen is the actual matter of formation and the part of the female is just to nourish and nurture; until it is proved by the modern science that both male and female gametes equally take part in the formation of the embryo. However, the Islamic Holy Scripture, the Quran, and the narrations from Islamic prophet (PBUH) and the descriptions of the Islamic scholars stand in opposition to these concepts and have a stunning correlation with the modern scientific descriptions of the embryology.